Disrupted theta oscillation propagation in healthy elderly individuals with apolipoprotein E epsilon 4 allele - Duho Sihn; Min-Ki Kim; Sung-Phil Kim (Frontiers in Neuroscience)
IntroductionThe apolipoprotein E epsilon 4 allele (APOE4) is one of the most influential genetic risk factors for late-onset Alzheimer’s disease (LOAD). Past studies have identified electroencephalogram (EEG) biomarkers in theta oscillations shared by both healthy individuals with APOE4 and patients with Alzheimer’s disease (AD), indicating the potentials of EEG biomarkers in healthy individuals with APOE4 for understanding and predicting LOAD. Since AD reveals a disconnection syndrome characterized by pathological synaptic connections that are also observed with APOE4, we aimed to investigate whether EEG oscillation propagation that could be influenced by impaired synaptic connections is disrupted in healthy individuals with APOE4.MethodsWe analyzed a publicly available EEG dataset of elderly healthy individuals with or without APOE4. We estimated theta oscillation propagation using the local phase gradient (LPG) method and computed the median LPG length that represented the consistency of propagation directions.ResultsWe found that the median LPG length of frontal midline theta oscillations was smaller in participants with APOE4 than those without APOE4.DiscussionThis finding indicates that APOE4 can lead to disruption in theta oscillation propagation of EEG, potentially predisposing individuals with APOE4 to LOAD.